Effectiveness of nursing-led microlearning with spaced reinforcement on sexual violence awareness among rural adolescents in Indonesia - Risnah Risnah; Muthahharah Muthahharah; Eka Hadrayani; Aisyah Bahar; Harmawati Harmawati; Muhammad Irwan; Sudarman Sudarman (International Journal of Public Health Science (IJPHS), 2026)
Sexual violence among adolescents remains a major public health concern, particularly in rural areas where access to prevention education is limited. This study evaluated the effectiveness of a nursing-led microlearning intervention with spaced reinforcement in improving adolescents’ awareness of sexual violence. A repeated-measures experimental study was conducted among 120 adolescents aged 13-16 years from rural junior high schools. Participants received either microlearning with spaced reinforcement (n = 60) or leaflet-based education (n = 60). Awareness was assessed at baseline, post-intervention, and four-week follow-up. Data were analyzed using linear mixed-effects models and generalized estimating equations. Baseline awareness scores were comparable between groups. Compared with leaflet education, the microlearning group demonstrated significantly greater improvements immediately after the intervention (β = 9.1, 95% CI: 7.2-11.0, p < 0.001) and maintained higher scores at follow-up (β = 8.6, 95% CI: 6.5-10.7, p